1983
DOI: 10.1111/j.1464-410x.1983.tb03357.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Carcinoembryogenic Antigen (CEA) in the Diagnosis and Follow‐up of Bladder Carcinoma

Abstract: The level of urinary carcinoembryogenic antigen (CEA) was evaluated in the diagnosis and follow-up of urothelial carcinoma of the bladder. Urinary CEA concentration, cystoscopic findings and the histopathology of an eventually resected bladder tumour were correlated in 177 cases. The sensitivity proved to be 34%, the specificity 82%. Possible correlations with sex, infection, primary tumour or recurrence, differentiation and invasion of an eventually resected tumour and influence of adjuvant therapy were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The simple presence of bacteria in the urine irrespective of their identity or number has no influence on urinary CEA [19]. It is the inflammation of the urothelium that is responsible for the production and release of CEA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simple presence of bacteria in the urine irrespective of their identity or number has no influence on urinary CEA [19]. It is the inflammation of the urothelium that is responsible for the production and release of CEA.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the tumor stage, some authors have found a correlation between it and the level of CEA in urine, the higher the stage the higher the level [3,5,23,24] However, others found no correlation [7,10,11,19,25] In this series, a definite relationship was found between the stage of malignancy and the levels of urinary CEA in the urine; the higher the stage the higher the level of CEA. On the other hand, serum CEA was in another study found to increases with increasing extent of cancer [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors found no correlation between the grade of malignancy and urine CEA levels [1,[5][6][7]19,25,26]. However, others have advocated that the less differentiated the tumor, the higher is the level of CEA in the urine [3].…”
Section: Discussionmentioning
confidence: 99%
“…These include sex, urinary tract infection, grade and stage of tumour, previous therapy and the assay method used. Several studies have employed commercial redioimmunoassay (RIA) kits from Roche or Abbott Labo ratories, and the upper limit of normal in healthy patients has been published from 1.5 ng/ml [fraget al, 1975] to 10 ng/ml [Tailly et al, 1983]. In our previous studies the upper limit was taken as 10 pg CEA/g creatinine, corre sponding to 10 ng/ml using the Abbott EIA assay [Cooper et al, 1985], Such a wide range of results would suggest that the assays may be detecting not only CEA but also substances with CEA-like activity.…”
mentioning
confidence: 99%